To be or not to be (e)sports? That is not the question! Why and how sport and exercise psychology could research esports - Leis, O.; Raue, C.; Dreiskämper, D.; Lautenbach, F. (German Journal of Exercise and Sport Research, 2021)
Whether esports can be considered a sport is highly debated. The German Olympic Sport Federation (DOSB) and the German Society for Sport Sciences (DVS) recently stated that esports should not be integrated into the canon of sport. Our aim is not to further fuel this debate but rather to argue that to be or not to be sport is not the most important question from a scientific perspective. After summarizing the current discussion on whether esports constitute a sport, this paper discusses why and how sport and exercise psychology (SEP), in particular, could research esports. To exploit research opportunities in esports, such as adapting validated methods and testing existing models, scholars in SEP could examine the aspects arising from its positional stance. We argue that the potential of SEP approaches, models, and methods, positions it well to play an important role in research on esports. The present perspective provides a starting point for a constructive discourse on the development of SEP and the potential for its role in esports research.